DESAIN PRODUK, KUALITAS PRODUK, CITRA MEREK DAN HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN GENERASI Y - Michael Reinout Adonis; Yunita Budi Rahayu Silintowe (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract This study aims to determine the effect of product design, product quality, brand image, and product prices on purchasing decisions on Honda PCX motorcycles in Generation Y in Salatiga City. This study uses a quantitative approach with the data used using primary data through a questionnaire. The questionnaire was taken by using purposive sampling technique. The number of samples used in this study were 118 respondents who were taken from Generation Y consumers. This research was conducted by using multiple regression analysis method and tested using SPSS. The test results show that product design, product quality, brand image have no effect on purchasing decisions, while product prices have a positive effect on purchasing decisions for Honda PCX motorbikes in generation Y.